Relations between Brazil and Spain under the Bolsonaro’s government - A. L. Esteves (Ибероамериканские тетради, 2021)
In this  article the   author examines in detail the   bilateral relations between Spain and Brazil during  the  presidency of  Jair Bolsonaro. In addition, the subject of this article is the opposition of EU governments to the   environmental  policies of  the   South  American country and the  disastrous policies of the  Brazilian authorities in the  fight  against the    COVID-19   pandemic.   President   Bolsonaro’s   negligence   of climate change  and Amazon deforestation has prompted European governments to openly oppose the  ratification of the  Mercosur – EU Free Trade Agreement, which  was signed in 2019 after 20 years of negotiations. In May  2016, the   parties agreed on  reciprocal terms, resulting in signing  of the  agreement. It also  included the  exchange of goods and services, essential investments and public procurements. All this was done in the  context of a global policy of protectionism amid a weakening role of the  WTO as a supporter of the  trade liberalization process.  Despite its  success,  countries such  as France,  Austria  and the  Netherlands stand against the  Mercosur – EU trade deal, which can halt  its  ratification. The  Spanish government, on  the   contrary, is lobbying for  ratification of  the   agreement. Madrid,  interested in benefiting from the  Bolsonaro government’s liberal economic policies, maintains strong ties  with  its  South  American partner.  The  author analyzes  the   transformation  of  Spain  from   a relatively  irrelevant partner of  Brazil in the   20th century to one of  the   main  investors directing significant resources to the Brazilian economy. We also assess the  results and challenges of the  Brazil – Spain strategic partnership in a broader context of the  Brazil – EU relations.